PENGARUH ELIT TERHADAP KEGAGALAN OTONOMI DAERAH DI KABUBAPATEN NIAS UTARA - Gea, Remiman (Jurnal Nawala Politika, 2017)
Area expansion is the development of an autonomous region into two or more autonomous regions. North Nias is one of the districts that was expanded from Nias in 2008. The purpose of this research is the influance of elites on the failure of regional autonomy in North Nias. The theory that was used is the elite theory according to Gaetano Mosca and  Pareto . The methods of this research is descriptive qualitative. The data collection techniques in this research are observation, in-depth interviews and documents. The results of this study found that the expansion of North Nias was based on elite consensus. The main reason for North Nias was expanded in 2008 was due to the economic and development gap and the geographical location of North Nias that is quite far from the central government so that the welfare of the community was not achieved. The involvement of the elite in the expansion of North Nias is felt, whether the political elite, the elite bureaucracy as well as the regional elite or regional figures because there is political dynamics in that fight. However, after nine years of expansion in North Nias, the impact of the expansion was not felt by the people of North Nias, but turns out the expansion of Nias Utara was unsuccessful. There are some factors that caused the failure of North Nias’ expansion such as Human Resources, the inability of local governments to manage the potency of Natural Resources and the failure of infrastructure development. The author analyzed that the failure factors of the North Nias’ expansion occurred because the North Nias’ expansion was forced by the stakeholders which are the elites or community leaders of North Nias.   Keywords: Area expansion, elites, dynamics, failure